(untitled) (Research, Society and Development, 2022)
Bisphosphonates are a class of compounds used to treat many different medical conditions. Its use has increased dramatically in recent years as new indications for its use have emerged. Current indications include the treatment of multiple myeloma, hypercalcemia, osteolytic lesions of metastatic disease, Paget’s disease, and, most commonly, osteoporosis. While these drugs are beneficial, a significant and potentially devastating complication - osteonecrosis of the jaws - has been reported termed bisphosphonate-related osteonecrosis (BRON), and has been increasingly recognized. In this context, this study aims to carry out a literature review regarding the main aspects of oral and maxillofacial surgery in patients undergoing therapy with bisphosphonates, and to report the clinical manifestations of mandibular osteonecrosis related to the drug in question. In order to achieve this objective, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect. The results indicate that, with the increasing use of bisphosphonates in the female population, BRON of the mandible is likely to be an increasing problem that will require complex treatment and management by oral and maxillofacial surgeons. As such, our expertise will be critical in providing answers to difficult questions of management and treatment outcomes. Unfortunately, at this time, only palliative care can be offered to patients suffering from this potentially devastating process. Increased awareness and vigilance can reduce potential complications. More studies looking at specific risk factors may help prevent this process before it starts.